(3GdTgGH GdhGeV aj CMcGe GdaQGFVs - (3GdMSjfj, GdMdj, GdfLaj, GdbRhjfj, eMeO egOj Hf GdMSf, J (B1300(3g`s ((3eQRG Hf YHGS Hf YdGhjs)
(3ChdgG (B:s
(3GdMeO ddg hGQK GdCQV(B... (3hHYO ajbhd(B... (3eYR GdOjf eMeO Hf GdMSf (B... (3ef jdRefj ELGHJg hdG jSYfj eNGdaJg(B...s
(3BNQgG (B:s
(3heJi bSeJ GdJQcI LeYJ MUd HGdbSeI (B... (3gPG BNQ eG ChQOfGg EjQGOg aj CMcGe GdaQGFV(B. (3hGdMeO ddg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B114s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis